A Mechanics Model for Contact with Rough Surface Considering the Interaction of Micro-Asperity Bodies - Yazhou Mao; Qingxin Hu; Yingying Yu; Shaolin Shi; Jiaming Pei; Zichen Li; Linyuan Wang (Lubricants)
In order to evaluate contact characteristics, a modified contact model was proposed considering the deformation characteristics of asperity bodies, and the variation rules of wear rate with fractal dimension, material property constant and debris probability were established. The results show that the actual contact area increases with an increase in load when the surface topography is constant, whereas the contact area decreases with an increase in characteristic scale coefficient if the fractal dimension or load is constant. For running-in wear, the wear rate increases with an increase in surface profile parameters under the same contact area. In addition, the wear rate increases with an increase in actual contact area when the surface profile parameter is constant. Regarding abrasive wear, the wear rate is the smallest when the fractal dimension is 1.6. The wear rate increases with an increase in contact area under the same characteristic scale coefficient, but decreases with an increase in the characteristic scale coefficient under the same contact area, and the smaller the material constant and the larger the probability constant, the higher the wear rate. The establishment of this model provides a basis for further study of the tribological properties of the contact surface.